1978
DOI: 10.1159/000136863
|View full text |Cite
|
Sign up to set email alerts
|

Accommodation Related to the Action of Ethanol on Frog Sciatic Nerve

Abstract: Index of accommodation of 32 frog sciatic nerves was studied with exponentially rising currents. Ethanol was mixed with normal Ringer’s solution at the following concentrations: 42, 85, 171, and 513 mM. We found a significant increase in the accommodation index. The results were attributed to the sodium conductance change and to a drop in membrane potential elicited by ethanol. The loss of the breakdown in the nerve accommodation curve was interpreted as the ethanol acting mainly on the thinner nerve fibres ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1980
1980
1983
1983

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Guttman (4), Quevedo et ai (6,8) and Vivaldi et al (10) pointed to nerve accommoda tion as the most sensitive electrophysiological parameter and suggested that this excitability index should be preferentially used. The basic fact in nerve accommodation is that any slowly rising current increases the threshold to the applied stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…Guttman (4), Quevedo et ai (6,8) and Vivaldi et al (10) pointed to nerve accommoda tion as the most sensitive electrophysiological parameter and suggested that this excitability index should be preferentially used. The basic fact in nerve accommodation is that any slowly rising current increases the threshold to the applied stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…The accommodation curves measured in the brachioradialis muscle, when the ERC had a time constant greater than 40 ms, showed a breakdown similar to that in nerves [14,16,17]. The breakdown in the accommodation curves of nerves has been considered to be due to the successive stimulation of different groups of fibers, with heterogeneous properties of excitability and accommodation [19,22].…”
Section: Discussionmentioning
confidence: 99%
“…Even though accommodation has been described as the most sensitive parameter of excitability in the conducting membrane [5,16] there is a total lack of documentation concerning the changes of this excitability parameter during hypoxic conditions. The study of the behavior of the muscle accommodation and the changes in the kalemia and resting membrane potential (RMP) in rats under hypoxic conditions induced by tourniquet, with high and low mortality, are the objects of this work.…”
Section: Introductionmentioning
confidence: 99%
“…Higher concentrations (>100 mM) cause a further depolarization, decreased sodium conductance, and the inactivation of sodium channels, resulting in a slower propagation velocity and a lower action potential amplitude (Seeman, 1972). Small unmyelinated fibres are affected more than larger myelinated fibres (Quevedo et al, 1978) .…”
Section: Electrophysiological Studies Indicate Golgi Cellsmentioning
confidence: 96%